2010
DOI: 10.1002/clc.20694
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Thrombocytopenia Among Patients Undergoing Intra‐aortic Balloon Pump Counterpulsation in the Coronary Care Unit

Abstract: Background: Thrombocytopenia Hypothesis: intra-aortic balloon pump (IABP)-associated thrombocytopenia is not associated with an increased risk of major bleeding or in-hospital death. Thrombocytopenia is a common adverse effect of the IABP. However, the clinical implications of IABP-associated thrombocytopenia are unknown. Methods: We assessed the incidence and predictors of thrombocytopenia, and the association between thrombocytopenia and relevant clinical end points, using prospectively collected data on 252… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
2
28
1
1
Order By: Relevance
“…This may indicate that coagulopathy that develops from a mechanical source has a lesser impact on bleeding and mortality. This finding is similar to previous studies that showed that thrombocytopenia secondary to IABP insertion was not associated with major bleeding or in‐hospital mortality, suggesting that thrombocytopenia that develops from a mechanical factor may have less clinical significance than thrombocytopenia that develops in a systemic illness . Studies have also shown that pre–cardiac transplant coagulopathy developing after cardiogenic shock is a marker of worse prognosis and increased bleeding and mortality, a finding that was used to support institution of MCS before shock‐induced coagulopathy to reduce risk of bleeding and graft failure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may indicate that coagulopathy that develops from a mechanical source has a lesser impact on bleeding and mortality. This finding is similar to previous studies that showed that thrombocytopenia secondary to IABP insertion was not associated with major bleeding or in‐hospital mortality, suggesting that thrombocytopenia that develops from a mechanical factor may have less clinical significance than thrombocytopenia that develops in a systemic illness . Studies have also shown that pre–cardiac transplant coagulopathy developing after cardiogenic shock is a marker of worse prognosis and increased bleeding and mortality, a finding that was used to support institution of MCS before shock‐induced coagulopathy to reduce risk of bleeding and graft failure.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to previous studies that showed that thrombocytopenia secondary to IABP insertion was not associated with major bleeding or in-hospital mortality, suggesting that thrombocytopenia that develops from a mechanical factor may have less clinical significance than thrombocytopenia that develops in a systemic illness. 13,35,36 Studies have also shown that pre-cardiac transplant coagulopathy developing after cardiogenic shock is a marker of worse prognosis and increased bleeding and mortality, 17 a finding that was used to support institution of MCS before shock-induced coagulopathy to reduce risk of bleeding and graft failure. However, findings from our subgroup analysis demonstrated a homogenous association of pre-HT coagulopathy and in-hospital mortality, both in patients with and in those without cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…A score ≤ 3 suggests a low pre-test probability for HIT, a score 4-5 an intermediate probability, and a score > 5 a high probability severe thrombocytopenia (defined as a platelet count <20 × 10 9 cells/L) vs 16% in the control arm [69]. For patients placed on an intra-aortic balloon pump, roughly 50% will develop thrombocytopenia [70,71].…”
Section: Step 6: Consider Hemodilutionmentioning
confidence: 99%
“…Platelet drop is usually mild and not associated with clinically significant bleeding. Patients on IABP frequently have concomitant heparin use for anticoagulation but the platelet drop is independent [ 26 ]. Continuous flow ventricular assist devices cause thrombocytopenia by causing platelet activation and aggregation due to non-pulsatile blood flow and mechanical shear stress [ 27 ].…”
Section: Thrombocytopenia Associated With Cardiac Assist Devicesmentioning
confidence: 99%